An Evaluation of the Linearity of Curriculum‐Based Measurement of Oral Reading (CBM‐R) Progress Monitoring Data: Idiographic Considerations. Issue 4 (27th June 2016) - Van Norman, Ethan R.; Parker, David C.
Abstract : Educators use curriculum‐based measurement of oral reading (CBM‐R) to measure student response to instruction. Current decision‐making frameworks assume students demonstrate linear growth across a school year. However, growth appears nonlinear for at least a subgroup of students. We assessed the degree to which grade two ( n = 800) and grade three ( n = 800) students receiving intensive interventions experienced discontinuous growth. We also explored when discontinuous growth tended to occur, and whether students improved or regressed afterward. Results indicate linear patterns were adequate for most students (80 percent). Students who showed discontinuous growth early tended to improve afterward. Conversely, students who showed discontinuous growth later tended to plateau. Findings suggest multilevel models may obscure variability in growth patterns. Practice and research implications are discussed.